Design and experimental analysis of rice pneumatic seeder with adjustable seeding rate - Xing, He; Wang, Zaiman; Luo, Xiwen; Zang, Ying; He, Siyu; Xu, Peng; Liu, Shuncai (International Journal of Agricultural and Biological Engineering, 2021)
To adapt to the diversity of hybrid rice and meet its requirements of precision seeding, a rice pneumatic seeder with adjustable seeding rates was designed in this study. The seeder employed an independent vortex pump to provide the air source for the seed metering device. According to the requirements of air flow in the seed metering device, a sub-pipeline and a general pipeline were designed. The performances of the two types of pipelines were verified by the air pressure uniformity tests. The results showed that the sub-pipeline can distribute the air pressure more evenly than the general pipeline. The coefficient of variation of the sub-pipeline pressure was less than 5%. Wuyou 1179 hybrid rice was selected as the experimental object. The field seeding tests were carried out with different negative pressures and different number of groups of sucking holes as experimental factors. The results showed that the average qualified rate of seeding was 93.35% when only 2 groups of sucking holes were working under the seed sucking negative pressure of 2.0 kPa. The average qualified rate of seeding was 87.21% when 3 groups of sucking holes were working under the seed sucking negative pressure of 1.6 kPa. The average qualified rate of seeding was 83.73% when 4 groups of sucking holes were working under the seed sucking negative pressure of 1.6 kPa. The average qualified rate of seeding was 79.86% when 5 groups of sucking holes were working under the seed sucking negative pressure of 1.6 kPa. The main factors affecting the seeding effect were analyzed and the feasibility of a rice pneumatic seeder with adjustable seeding rates was verified by field tests. The research results can provide a basis for its practical production and application. Keywords: agricultural machinery, adjustable seeding rate, seeder, pneumatic, rice, pipeline DOI: 10.25165/j.ijabe.20211404.5658 Citation: Xing H, Wang Z M, Luo X W, Zang Y, He S Y, Xu P, et al. Design and experimental analysis of rice pneumatic seeder with adjustable seeding rate. Int J Agric & Biol Eng, 2021; 14(4): 113–122.